Improving Student Learning Outcomes on Heat Material Using the Stem Approach at SMP Negeri 2 Juli - Khairunnisak; Fatma Zuhra; Milda Husda (Journal Informatic, Education and Management (JIEM), 2024)
This study aims to examine the effectiveness of the STEM (Science, Technology, Engineering, and Mathematics) approach in improving student learning outcomes on heat material at SMP Negeri 2 Juli. The research employs an experimental method with a pre-test and post-test design involving two groups of students: an experimental group that received instruction using the STEM approach and a control group that used conventional methods. The results show that students who participated in learning with the STEM approach experienced a significant improvement in their understanding of heat concepts, as reflected in the higher average post-test scores compared to the control group. These findings indicate that the STEM approach is not only effective in enhancing learning outcomes on heat material but also motivates students to be more active, creative, and critical in the learning process. Therefore, the STEM approach is recommended for broader implementation in science education at SMP Negeri 2 Juli.